Antioxidant capacity of phoenix dactylifera linn extract and the effects towards calcium channel antagonist in the withdrawal syndrome of morphine induced rats - Ibrahim Haruna Sani; Universiti Sultan Zainal Abidin . Faculty of Health Sciences (2015)
Date fruit (Phoenix dactyli/era linn) is remarkable known for it is nutritional and numerous health benefits due to its presence of bioactive compounds. The mariami date are widely found and used by Malaysians especially in Terengganu. However, previous literatures have shown that the presence of phenolic contents in the natural plant products is crucial to vita} human body systems inc1uding central nervous system. There is growing evidence indicating that calcium channels play an important role in the mechanism of morphine dependence and withdrawal syndrome. The aim of the study was to examine the effects of phenolic compound contained in date fruit extract towards calcium channel antagonists in the treatment of withdrawal syndrome in morphine dependent rats. The total phenolic contents (TPC) and total flavonoid contents (TFC) were determined using Folin-calculate method and aluminium chloride method respectively. A total of thirty six (n=36) 'prague-dawley rats (weight 200- 220g) adult male rats were injected subcutaneously with morphine twice per day for 5 days to induce morphine dependence. An escalating doses of morphine from 10 to 60mglkg over a period of 5 days. Morphine administration was ceased on day 5, an equal number of rats were assigned to one of nine groups, which incl ntrol (received morphine only), positive control (nifedepine), negative control (normal saline) and the groups, which received either acute or chronic extract administration. The withdrawal syndrome was precipitated by intra-peritoneal injection of opioid antagonist (naloxone) 2 hours after last morphine injection. The rats were immediately observed for the presence of withdrawal sign (jumps, tremor, eye ptosis, teeth chattering, wet dog shaking, diarrhoea and urination) over the period of 30 minutes. The results indicated a statistically significant mean difference of repeated injection of extracts and nifedipine at (P<O.OOl), this suppressed withdrawal syndrome in morphine dependent rats. On the other hand, a single injection of the extract and nifedipine does not exert a statistically significant effect, especialJy on the hyperactivity sign (tremor, eye ptosis, teeth chattering and wet dog shaking). The effects of date extract on morphine dependent rats result in significant reduction of withdrawal symptom especially after chronic extract administration. The outcome of the study suggested that the presence of phenolic compound might have both calcium channel antagonist activity, reversal of neuronal adaptation that take place during mechanism of morphine dependence and can serve as an appropriate treatment of opioid addiction.
1. Introduction -- 2. Literature review -- 3. Methodology -- 4. Results and discussions -- 5. Conclusion
Thesis (Degree of Master of Science) - Universiti Sultan Zainal Abidin, 2015
Includes bibliographical references (leaves 62-72)
Keywords: Universiti Sultan Zainal Abidin -- Dissertations; Universiti Sultan Zainal Abidin -- Faculty of Health Sciences -- Dissertations; Dates (Fruit); Dissertations, Academic